An additional patient with SMAD4‐Juvenile Polyposis‐Hereditary hemorrhagic telangiectasia and connective tissue abnormalities: SMAD4 loss‐of‐function and gain‐of‐function pathogenic variants result in contrasting phenotypes. Issue 10 (23rd July 2022) - Gheewalla, Gregory M.; Luther, Jay; Das, Saumya; Kreher, Jeffrey B.; Scimone, Eleanor R.; Wong, Ashley W.; Lindsay, Mark E.; Lin, Angela E.
Abstract: Loss‐of‐function pathogenic variants in somatic and germline cells in SMAD4 may cause cancer and juvenile polyposis‐Hereditary Hemorrhagic Telangiectasia ( SMAD4‐ JP‐HHT), respectively. In a similar manner, gain‐of‐function somatic and germline pathogenic variants in SMAD4 can cause various forms of cancer as well as Myhre syndrome. The different SMAD4 molecular mechanisms result in contrasting clinical phenotypes demonstrated by SMAD4 ‐JP‐HHT and Myhre syndrome. We report an additional patient with SMAD4 ‐JP‐HHT and aortopathy, and expand the phenotype to include severe valvulopathy, cutaneous, ophthalmologic, and musculoskeletal features consistent with an inherited disorder of connective tissue. We compared this 70‐year‐old man with SMAD4 ‐JP‐HHT to 18 additional literature cases, and also compared patients with SMAD4 ‐JP‐HHT to those with Myhre syndrome. In contrast to aorta dilation, hypermobility, and loose skin in SMAD4 ‐JP‐HHT, Myhre syndrome has aorta hypoplasia, stiff joints, and firm skin representing an intriguing phenotypic contrast, which can be attributed to different molecular mechanisms involving SMAD4 . We remind clinicians about the possibility of significant cardiac valvulopathy and aortopathy, as well as connective tissue disease in SMAD4 ‐JP‐HHT. Additional patients and longer follow‐up will help determine if more intensive surveillance improves care amongst these patients.